Hubungan Pemberian Slow Deep Breathing dan Aromaterapi Chamomile dengan Perubahan Tekanan Darah - Andara Martika; Luhut Simpora; Kalia Suhiliu (Journal of Applied Health Sciences, 2025)
Hypertension is one of the major global health problems that increases the risk of cardiovascular diseases and mortality. Non-pharmacological approaches such as relaxation techniques and aromatherapy have been considered effective in helping to reduce blood pressure. This study aimed to investigate the relationship between the application of slow deep breathing (SDB) combined with chamomile aromatherapy and changes in blood pressure among individuals with hypertension. A quasi-experimental design with a pre-test post-test approach without a control group was employed. The study involved 30 respondents selected through purposive sampling based on inclusion criteria. The SDB intervention was conducted for 10 minutes accompanied by chamomile aromatherapy inhalation via a diffuser, administered once daily for seven consecutive days. Blood pressure was measured using a sphygmomanometer before and after the intervention. Data analysis using a paired t-test demonstrated a significant reduction in systolic blood pressure (p = 0.001) and diastolic blood pressure (p = 0.003) following the intervention. The mean reduction in systolic blood pressure was 8.4 mmHg, while diastolic blood pressure decreased by 5.2 mmHg. These findings indicate that the combination of SDB and chamomile aromatherapy is effective in reducing blood pressure, possibly through the mechanisms of lowering sympathetic nervous system activity and the relaxation effects of volatile chamomile components. This intervention is recommended as a complementary therapy option for hypertensive patients to support conventional medical treatment.